El método tomatis - Moreno López, Mayra Alexandra (2017)
The research on the Tomatis Method was deployed under the premise of examining the benefits of the Tomatis method through auditory stimulation for the treatment of children with learning difficulties, considering that there is a low knowledge of the method of auditory stimulation in the treatment of learning disorders. In order to achieve the research objectives, a documentary bibliographic design methodology has been used to abstract the scientific and theoretical contents that allow to deepen the knowledge of Tomatis Method and its contribution in the treatment of different disorders of the people, on the other hand the design of field was applied with the collection of data from parents, doctors and director of the Center of Stimulation Tomatis in Quito. The research has collected data of qualitative and quantitative type that have made possible the description about the results achieved with the application of auditory stimulation….